2020
DOI: 10.7554/elife.58906
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of computer code relies primarily on domain-general executive brain regions

Abstract: Computer programming is a novel cognitive tool that has transformed modern society. What cognitive and neural mechanisms support this skill? Here, we used functional magnetic resonance imaging to investigate two candidate brain systems: the multiple demand (MD) system, typically recruited during math, logic, problem solving, and executive tasks, and the language system, typically recruited during linguistic processing. We examined MD and language system responses to code written in Python, a text-based program… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 152 publications
(159 reference statements)
4
61
1
Order By: Relevance
“…The third was on the right middle frontal gyrus (MFG) extending to the adjacent right superior and inferior frontal gyri. In contrast to several previous studies (Siegmund et al, 2014; Liu et al, 2020; Ivanova et al, 2020; Peitek et al, 2021), left parietal regions such as angular gyrus and inferior parietal lobule were not observed in our MKDA result at the significant threshold.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The third was on the right middle frontal gyrus (MFG) extending to the adjacent right superior and inferior frontal gyri. In contrast to several previous studies (Siegmund et al, 2014; Liu et al, 2020; Ivanova et al, 2020; Peitek et al, 2021), left parietal regions such as angular gyrus and inferior parietal lobule were not observed in our MKDA result at the significant threshold.…”
Section: Resultscontrasting
confidence: 99%
“…The indicator maps taken from Ikutani et al (2020) and Peitek et al (2021) had slightly different patterns but still showed Language and Semantic within the top-3 largest correlations. Two indicator maps taken from contrasts of [Program output estimation > Output estimation from sentence] in Ivanova et al (2020) were grouped by the unique cluster in our HCA dendrogram, having very small correlations to the language-related terms. The indicator map of ScrachJr in Ivanova et al (2020) showed a different pattern than others.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations